MiR-494 induces metabolic reprogramming through G6pc targeting and modulates sorafenib response in hepatocellular carcinoma. (March 2023) - Galvani, G.; Leoni, I.; Bergamini, C.; Rizzardi, N.; Melli, M.; Coada, C.A.; Monti, E.; Giovannini, C.; Liparulo, I.; Ferracin, M.; Ravaioli, M.; Cescon, M.; et al.
Abstract : Introduction: The epidemiology of hepatocellular carcinoma (HCC) in industrialized countries is increasingly related to metabolic syndrome and non-alcoholic steatohepatitis (NASH). Despite the approval of molecular targeted drugs, including immune checkpoint inhibitors, the lack of circulating biomarkers still impacts patient responsiveness to treatments, as evidenced by reduced sensitivity to immunotherapy in NASH-associated HCCs. In this context, there is an urgent need to identify new biomarkers to help stratify patients according to personalized therapeutic regimens. Aim: The aims of this work are to study metabolic mechanisms underlying miR-494 overexpression in HCC preclinical models and to assess miR-494 as a circulating biomarker associated with metabolic features and sorafenib resistance in HCC patients. Materials and Methods: We identified miR-494 metabolic targets through bioinformatics analysis. QPCR analysis of glucose 6-phosphatase catalytic subunit (G6pc) was performed in preclinical models and HCC patients. Functional and metabolic analyses assessed G6pc targeting and miR-494 involvement in metabolic change, mitochondrial dysfunction, and ROS production in HCC cells. Live-imaging analysis elucidated the involvement of miR-494/G6pc axis in cell proliferation of HCC cells under stressful conditions. Circulating miR-494 levels were assayed in sorafenib-treated HCC patients and DEN-HCC rats. Results: We demonstrated that miR-494 promote a metabolic shift of HCC cells towards a glycolytic phenotype trough G6pc targeting. The miR-494/G6pc axis exhibits an active role in the metabolic plasticity of tumor cells promoted by glycogen and lipid droplets accumulation to be used under detrimental conditions. High miR-494 serum levels are predictive of sorafenib resistance in a small cohort of HCCs and identify patients with metabolic derangements. AntagomiR-494-based strategies showed a synergic effect with metabolic inhibitors and sorafenib in HCC cells. Conclusions: Our preliminary data suggest miR-494 as a possible target for combined treatments and a promising biomarker for the identification of patients with dysmetabolic HCCs who may be refractory to currently approved treatments.